2016
DOI: 10.4103/0019-5545.174381
|View full text |Cite
|
Sign up to set email alerts
|

Perception, knowledge, and attitude toward mental disorders and psychiatry among medical undergraduates in Karnataka: A cross-sectional study

Abstract: Context:Globally, psychiatry as a subject, psychiatrists as professionals, and patients with psychiatric disorders are subjected to cultural stereotypes and negative attitude by the general population. What is of alarming concern is that these prejudices exist within the medical community as well.Aims:This study aims at evaluating the perception, knowledge, and attitude toward psychiatric disorders, therapeutic modalities used in psychiatry, psychiatry as a subject and psychiatrists as professionals among unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
42
2
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 17 publications
5
42
2
3
Order By: Relevance
“…A more recent study from Karnataka found that psychiatrists are increasingly seen in a positive light by medical students, however it remains to be seen if this is a general trend within Indian societies (Aruna et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…A more recent study from Karnataka found that psychiatrists are increasingly seen in a positive light by medical students, however it remains to be seen if this is a general trend within Indian societies (Aruna et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…[17] The undergraduate medical student population had significant shortcomings in knowledge and attitude pertaining to psychiatric disorders, more glaring in the initial years of education. [18] Sireesha SR et al in their study highlighted that exposure to psychiatry posting partially improving the attitude of medical students towards mental illness. [19] CONCLUSION This study explored the attitude of nurses towards mental illness in tertiary level general hospital settings.…”
Section: Discussionmentioning
confidence: 99%
“…An integrative review has revealed the paucity of adequate mental health educational preparation among general health professionals who are required to deliver different level of care to patients of mental illness in various healthcare settings [10]. Studies revealed that general healthcare professionals had significant shortcomings in knowledge and attitude pertaining to psychiatric disorders, which hinder the provision of adequate and appropriate services [10] [11].…”
Section: Experiential Mental Health Training For Health Professionalsmentioning
confidence: 99%